Effect of Austenite Grain Size on the Bainitic Transformation in a 690 MPa Grade High-Strength Multi-Functional Construction Steel - Zhenye Chen (Metals, 2022)
A high-strength low-carbon construction structural steel was investigated in the laboratory. The various austenite grain sizes were obtained by austenitizing the steel at different temperatures. The effect of austenite grain size on bainite transformation was studied by the dilatometer. The results show that the microstructure of high-strength low-carbon structural steels mainly includes granular bainite, lath-like bainite and martensite-austenite (M-A). The microstructure changes from granular bainite to lath-like bainite with the increase in austenitizing temperature or austenite grain size. When the samples were heated at the lower temperature of 860 °C, the bainite starting temperature was relatively high, which was mainly attributed to the promotion of the granular bainitic nucleation and the formation of the solute-depleted regions in the austenite. Compared to 860 and 1260 °C, the bainite transformation rate in the specimen austenitized at 1000 °C is the highest because of the small prior austenite grain size and larger transformation driving force.